Pemahaman Masyarakat Terhadap Sanitasi Lingkungan (Studi di Gampong Asan Kumbang Kecamatan Bandar Dua Kabupaten Pidie Jaya) - Maria Ulfa (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2018)
ABSTRAKPenelitian ini bertujuan untuk mengetahui pemahaman masyarakat terhadap sanitasi di Gampong Asan Kumbang Kecamatan Bandar Dua Kabupaten Pidie Jaya, dan peran masyarakat dalam menjaga sanitasi lingkungan di Gampong Asan Kumbang Kecamatan Bandar Dua Kabupaten Pidie Jaya. Analisis data menggunakan teori tindakan sosial oleh Max Weber, tindakan merupakan suatu perbuatan, perilaku, atau aksi yang dilakukan oleh manusia sepanjang hidupnya, guna mencapai tujuan tertentu. Dalam kajian sosiologis, tindakan dapat dilihat sebagai perilaku otomatis seseorang yang tidak melibatkan proses pemikiran dalam melakukan tindakan Jenis penelitian deskriptif dengan menggunakan pendekatan kualitatif. Pengumpulan data dilakukan dengan observasi, wawancara dengan informan yang memenuhi kriteria subjek penelitian,serta relevan dalam memberikan informasi yang dibutuhkan dalam penelitian ini. Berdasarkan hasil penelitian dapat diambil kesimpulan bahwa rendahnya pengetahuan dan pemahaman masyarakat tentang pentingnya sanitasi lingkungan yang sehat terlihat dari perilaku masyarakat yang kurang ramah pada lingkungannya. Seperti yang terjadi pada masyarakat gampong Asan Kumbang pemahaman dan kesadaran untuk menjaga kebersihan masih sangat kurang, terlihat dari kurangnnya kesadaran masyarakat terhadap kebersihan lingkungan sungai, tidak saling menjaga terhadap sarana yang disediakan, ada beberapa faktor yang menyebabkan masyarakat masih memanfaatkan sungai antara lain: faktor keuangan dan kenyamanan terhadap penggunaan sungai. Selanjutnya adapun peran masyarakat disini adalah hanya bergotong royong dan ikut berpatisipasi dalam membersihkan lingkungan.Kata Kunci: Pemahaman, Sanitasi, Lingkungan.ABSTRACTThe purpose of this research is to know people's understanding of sanitation in Gampong Asan Kumbang Kecamatan Bandar Dua Kabupaten Pidie Jaya, and the role of society in maintaining environmental sanitation in Gampong Asan Kumbang Kecamatan Bandar Dua Kabupaten Pidie Jaya. The theory in this study using the theory of social action by Max Weber, Action is an act, behavior, or action undertaken by humans throughout his life, in order to achieve certain goals. In sociological studies, Action can be seen as an automatic behavior of a person who does not involve the process of thinking in doing the action Type of descriptive research using a qualitative approach. Data collection is done by observation, interview with informants who meet the criteria of research subjects, and relevant in providing information needed in this research. Based on the results of the research can be concluded that the public understanding of environmental sanitation, Low knowledge and understanding of the importance of healthy environmental sanitation seen from the behavior of people who are less friendly to the environment. As happened in the gampong Asan Kumbang community, the understanding and awareness to maintain cleanliness is still lacking, the lack of awareness of the community towards the cleanliness of the river environment, not mutually guarding against the facilities provided, the financial factor and the convenience of the river usage. Furthermore, as for the role of society here is just mutual cooperation and participate in cleaning the environment.Keywords: Understanding, Sanitation, Environment.Society's Understanding Against Environmental Sanitation (Study at Gampong Asan Kumbang District Bandar Dua, Pidie Jaya Disricts) ABSTRACTThe purpose of this research is to know people's understanding of sanitation in Gampong Asan Kumbang Kecamatan Bandar Dua Kabupaten Pidie Jaya, and the role of society in maintaining environmental sanitation in Gampong Asan Kumbang Kecamatan Bandar Dua Kabupaten Pidie Jaya. The theory in this study using the theory of social action by Max Weber, Action is an act, behavior, or action undertaken by humans throughout his life, in order to achieve certain goals. In sociological studies, Action can be seen as an automatic behavior of a person who does not involve the process of thinking in doing the action Type of descriptive research using a qualitative approach. Data collection is done by observation, interview with informants who meet the criteria of research subjects, and relevant in providing information needed in this research. Based on the results of the research can be concluded that the public understanding of environmental sanitation, Low knowledge and understanding of the importance of healthy environmental sanitation seen from the behavior of people who are less friendly to the environment. As happened in the gampong Asan Kumbang community, the understanding and awareness to maintain cleanliness is still lacking, the lack of awareness of the community towards the cleanliness of the river environment, not mutually guarding against the facilities provided, the financial factor and the convenience of the river usage. Furthermore, as for the role of society here is just mutual cooperation and participate in cleaning the environment.Keywords: Understanding, Sanitation, Environment.